Spineless cactus varieties resistant to carmine cochineal (Dactylopius sp.) on the composition and sensory properties of goat milk - Beatriz Dantas Oliveira Fernandes; Rita de Cássia Ramos do Egypto Queiroga; Roberto Germano da Costa; Divan Soares da Silva; Mariana de Lima Maciel; Alenice Ozino Ramos; Ariosvaldo Nunes de Medeiros (Acta Scientiarum. Animal Sciences, 2020)
The physical-chemical characteristics and sensory attributes of milk are variable. This study aimed to evaluate how spineless cactus varieties resistant to carmine cochineal (Dactylopius sp.) influences the composition and sensory characteristics of goat milk. Twelve lactating goats with body weights of 51.35 ± 3.75 kg were distributed in a 4 × 4 Latin square, with three simultaneous squares composed of four animals, four periods, and four experimental diets: Control - goats fed tifton grass hay and concentrate; SCOE - goats fed the Orelha-de-elefante spineless cactus, tifton hay, and concentrate; SCB – goats fed the Baiana spineless cactus, tifton hay, and concentrate; SCM – goats fed the Miúda spineless cactus, tifton hay, and concentrate. The levels of protein and non-greasy solids and the sensory attributes of the milk (odor, butter flavor, and global acceptance) did not differ between the treatments (p > 0.05). The lipid content of the milk was reduced in the SCOE treatment compared to the control (p = 0.0014). The milk obtained from animals fed the SCOE and SCM treatments had a stronger flavor (p < 0.05). These results suggest that varieties of spineless cactus resistant to carmine cochineal can be used as goat feed without affecting milk production or global acceptance.